PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY PADA SISWA KELAS VII D SEMESTER GANJIL MTs NEGERI MAGUWOHARJO - Iffa Alwafi; Hidayati Hidayati; Tias Ernawati (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2014)
The purpose of this research was to increase the activeness and result of science learning through cooperative learning model with type Two Stay Two Stray at class D seventh grade student’s on odd semester of MTs N Maguwoharjo in year 2014/2015. The kind of this research was Classroom Action Research. The subjects of this research were class D seventh grade students of MTs N Maguwoharjo which amount to 33 students. The object of this research was the activeness and result of science learning through cooperative learning model with type Two Stay Two Stray. The data collection tecnique of this study was conducted by observation, field note, tests and documentation. The result of this study showed that, the student’s activeness and result of science learning have increased. This was indicated by the percentage of the activeness before the model conducted amount to 46,63% become 69,77% on first cycle and increased more as 85,15% on second cycle. The students learning result also have increased. The average  of students grade from the first grade as 62,35 on the students (36,36%) that fullfilles KKM increased to 67,42 on 22 students (66,7%) that fullfilles KKM on first cycle. Where as on second cycle the average of students grade increased to 80,24 on 25 student’s (75,76%) that fullfilled KKM.